2004
DOI: 10.2337/diabetes.53.9.2322
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Role of Glucocorticoids on Pancreas Development

Abstract: To determine whether glucocorticoids are involved in pancreas development, glucocorticoid treatment of rat pancreatic buds in vitro was combined with the analysis of transgenic mice lacking the glucocorticoid receptor (GR) in specific pancreatic cells. In vitro treatment of embryonic pancreata with dexamethasone, a glucocorticoid agonist, induced a decrease of insulin-expressing cell numbers and a doubling of acinar cell area, indicating that glucocorticoids favored acinar differentiation; in line with this, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 46 publications
11
100
1
1
Order By: Relevance
“…From our previous work investigating the direct effects of glucocorticoids on pancreatic development, by inactivating the GR either in all pancreatic progenitors (GR Pdx-Cre mice) or specifically in insulin-producing cells (GR RIP-Cre mice), we concluded that the GR is not necessary for beta cell development but rather prevents it through a direct effect on pancreatic progenitors [29]. By studying mice deleted for GR in the whole organism (GR null/null mice), we show here that GR is not required for the early induction of pancreatic development and differentiation but is nevertheless necessary in the pancreatic environment, and thereby through indirect effects, for pancreatic morphogenesis during late fetal development.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…From our previous work investigating the direct effects of glucocorticoids on pancreatic development, by inactivating the GR either in all pancreatic progenitors (GR Pdx-Cre mice) or specifically in insulin-producing cells (GR RIP-Cre mice), we concluded that the GR is not necessary for beta cell development but rather prevents it through a direct effect on pancreatic progenitors [29]. By studying mice deleted for GR in the whole organism (GR null/null mice), we show here that GR is not required for the early induction of pancreatic development and differentiation but is nevertheless necessary in the pancreatic environment, and thereby through indirect effects, for pancreatic morphogenesis during late fetal development.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have suggested that fetal overexposure to glucocorticoids can alter pancreatic development and thereby programme consequences for glucose homeostasis in the adult [28,29,34]. From our previous work investigating the direct effects of glucocorticoids on pancreatic development, by inactivating the GR either in all pancreatic progenitors (GR Pdx-Cre mice) or specifically in insulin-producing cells (GR RIP-Cre mice), we concluded that the GR is not necessary for beta cell development but rather prevents it through a direct effect on pancreatic progenitors [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations